Live Feedback for Immersive Music Performances - A Case Study - Amarie, Nicusor; Fadda, Gianluca; Popescu, Vlad; Ghenta, Jean-Marius; Murroni, Maurizio; Simiscuka, Anderson Augusto (Proceedings of the ACM International Conference on Interactive Media Experiences Workshops (IMXw); 2025: Proceedings of the ACM International Conference on Interactive Media Experiences Workshops, 2025)
This paper presents the architecture of an Extended Reality (XR) system for real-time streaming and spatial rendering of live music performances, along with a comprehensive setup for the acquisition of multichannel audio and three-dimensional performer motion data. The system enables remote users to experience live performances in immersive virtual environments, where each musician is represented by an avatar. Audio input is captured via a digital mixing console, enabling the transmission of synchronized multitrack audio streams using low-latency networking protocols. These streams are spatially rendered within a 3D scene using advanced audio spatialization techniques integrated into standard real-time engines such as Unity. The system also supports bidirectional interaction: audience-generated audio feedback (e.g., cheering, clapping, or singing) is captured, spatially processed, and reintroduced into the performance environment, enhancing performer-audience engagement through immersive, real-time crowd response. The architecture was set-up and initially tested in a real concert environment at the Rockstadt Club in Bras, ov, Romania, with the occasion of a live blues concert in 2024.